The water–energy–food (WEF) nexus as a tool to develop climate change adaptation strategies: a case study of the Buffalo River Catchment, South Africa - Dlamini, N.; Senzanje, A.; Mabhaudhi, Tafadzwanashe (IWA Publishing, 2023)
The Buffalo River catchment in KwaZulu-Natal, South Africa, has limited water resource infrastructure development, and climate change is predicted to increase its water supply deficits by exacerbating water distribution inequalities. This study evaluates and optimises current climate change policy plans on the Buffalo River catchments water system to aid in assessing the sustainability of policies that address the aforementioned challenges. The water–energy–food (WEF) nexus approach, which encourages system thinking by considering interconnections among water, energy, and food resources when developing integrated natural resource management strategies, was used to perform the evaluation. The water system's reliability in meeting projected domestic, agricultural, and energy water demands under climate change conditions was used for gauging the sustainability of the development plans. Findings projected the existing water policy plans to increase the domestic water provision by >70% under climate change; however, the <3% increase in irrigation and energy generation water demand coverage yielded a significant contrast in reliability between densely populated areas and regions with extensive agricultural activities. The optimised policy plans, which improved water provision for all considered sectors increased by >20% under climate change, are thus recommended for future water resource management research and dialogue in the Buffalo River catchment.